Impact of University Reputation and Academic Quality on University Selection Among Vietnamese Postgraduate Students: A Moderation Analysis of Gender - Azadeh Amoozegar; Ly Bao Duy Nguyen; Hariharan N. Krishnasamy; Boonyarit Omanee; Asokan Vasudevan (Education Sciences)
This study investigated the phases involved in postgraduates’ decision-making process when selecting a university in Vietnam. By analyzing the key factors that influence these decisions, the research provides insights into how these elements impact students’ university choices, offering a deeper understanding of enrolment behavior in the Vietnamese educational context. The survey was conducted by gathering quantitative data. With an emphasis on gender moderating university choice decisions, a 16-item questionnaire was used to measure university reputation and academic quality. Utilizing a quantitative approach, data were collected from a sample of postgraduate students and analyzed using Structural Equation Modeling (SEM) via SmartPLS 4. The results reveal that both university reputation and academic quality significantly influence university choice decisions. However, the moderating effect of gender on these relationships was found to be insignificant. These findings contribute to the limited literature on higher education marketing in Vietnam, particularly concerning postgraduate students, and offer valuable insights for university administrators. This study is in line with SDG 5 (Gender Equality), which includes topics like gender parity, inclusive participation, and gender equity, and SDG 4 (Quality Education), which highlights the significance of academic quality and reputation when choosing a university.